Designing and evaluating a high interactive augmented reality system for programming learning - Yi-Ming Kao, Gloria; Ruan, Cheng-An (Computers in human behavior, 2022)
Programming plays a pivotal role in Science, Technology, Engineering, and Mathematics (STEM) education. However, programming concepts and syntax are extremely abstract. We developed an augmented reality (AR)-based learning system to make programming concepts tangible. Specifically, we adopted a high interactive AR mode that allows students to freely assemble puzzle cards to compare various 3D animated programming results. This study adopted a quasi-experimental design and recruited 98 fifth graders as participants. Three groups, named the high interactive AR, low interactive AR, and the traditional learning (control) groups, were formed. The results revealed that the AR-based instruction, especially the high interactive AR mode, helped the students improve their programming achievements, gain higher learning motivation, reduce their cognitive load, and acquire a high degree of technology acceptance. The interview data mainly showed that the students in the high interactive group attained more positive experiences of assembling puzzle cards to learn programming. Our study suggests that using AR technology alone did not facilitate learning motivation, although it did produce better programming achievements compared to the traditional learning. A high interactive design such as “puzzle cards” is vital for arousing higher motivation, which can in turn facilitate a more in-depth understanding of programming logic. [Display omitted] •A special “puzzle card” AR system was applied to observe the dynamics of programming logic.•Students' logic performance was better in AR mode than in traditional instruction.•High and low interactive AR had high technology acceptance and low cognitive load.•Students' learning motivation was better for high than for low interactive AR mode.•High interactive AR allows for a more comprehensive exploration of concepts.